HOW EFFECTIVE IS VISUAL CONTENT IN DIGITAL MARKETING CAMPAIGNS FOR MSMEs? - Muh. Husriadi; La Ode Ramalan; Wa Ode Harliyanti (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The development of digital technology has changed the way MSMEs interact with customers, but many still have difficulty implementing effective marketing strategies. This study aims to analyze the effectiveness of visual content in digital marketing campaigns for MSMEs. The method used is a qualitative approach with in-depth interviews and content analysis from 10 MSMEs that are active on social media. The results of the study indicate that the use of visual content, such as short videos and infographics, increases customer interaction, market reach and sales. Engagement metrics such as views, likes, and comments provide important insights into audience response. The implications of these findings emphasize the importance of a planned visual content strategy to increase MSME engagement and sales in the digital era. This study recommends the use of easily accessible design tools and regular measurement of content effectiveness to achieve optimal results.